2022
DOI: 10.1007/s11249-022-01625-z
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Set-Up for In Situ Measurement and Mapping of Lubricant Film Thickness in a Model Rolling Bearing Using Interferometry and Ratiometric Fluorescence Imaging

Abstract: This paper describes a unique experimental set-up constructed for studies of lubricant behaviour in an operating rolling element bearing including in situ quantitative measurements of film thickness in and around the element-raceway contact. The set-up is based on a deep groove ball bearing in which the outer race is made of sapphire to allow full optical access to the zone in which the rolling elements are loaded against it. This allows direct imaging of lubricant films under both steady-state and transient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…When Coy et al [8] compared the thrust bearing film thickness measurements with the ball-on-disc test, they found that the major cause of the bearing's decreasing thickness was an inadequate supply of grease in the contact region. Utilizing the optical method, Chennaui M et al [9] found that the oil film thickness in the contact area of a model bearing is lower than that predicted by the elastohydrodynamic lubrication (EHL) theory due to oil starvation. Gonçalves et al [10] discovered that as soon as starvation starts, the grease film thickness decreases with increasing speed.…”
Section: Introductionmentioning
confidence: 99%
“…When Coy et al [8] compared the thrust bearing film thickness measurements with the ball-on-disc test, they found that the major cause of the bearing's decreasing thickness was an inadequate supply of grease in the contact region. Utilizing the optical method, Chennaui M et al [9] found that the oil film thickness in the contact area of a model bearing is lower than that predicted by the elastohydrodynamic lubrication (EHL) theory due to oil starvation. Gonçalves et al [10] discovered that as soon as starvation starts, the grease film thickness decreases with increasing speed.…”
Section: Introductionmentioning
confidence: 99%
“…They combined laser-induced fluorescence and light emitting diode (LED) illumination with two high-speed cameras and simultaneously observed the radial and axial directions of the bearing up to a rotational speed of 5,000 min -1 . Chennaoui et al (2022) measured the oil-film thickness between the ball and outer ring under oil-lubricated conditions using a 6206-type deep-groove bearing with a sapphire outer ring by applying the ultrathin film interferometry method, commonly used in ball-on-disc tests. A triggering system enabled the capture of images when a ball passed the uppermost point of the bearing, independent of the rotational speed, and fluorescence methods were used to observe the oil distribution.…”
Section: Introductionmentioning
confidence: 99%
“…For investigating the behaviors of lubricating oil films inside bearing, many studies employed ball-on-disc experiments using optical interferometry [3][4][5][6][7][8][9] or computational analyses based on the elastohydrodynamic lubrication (EHL) theory [10][11][12][13] to determine the oil film thickness, and only a few studies used actual bearing configuration. In a recent study, a sapphire outer ring with actual bearing shape was used for measuring the film thickness with optical interferometry [14], but the maximum rotational speed was 2,900 min −1 . No report can be found on the state of lubrication in actual bearings at speeds above 10,000 min −1 .…”
Section: Introductionmentioning
confidence: 99%